Corrigendum: Mitochondrial and apicoplast genome copy abundances of haemosporidian parasites are explained by host species and parasitic lineage(Front. Ecol. Evol., (2024), 12, (1305418), 10.3389/fevo.2024.1305418) - Brandler, Tim; Chakarov, Nayden (Frontiers in Ecology and Evolution, 2024)
In the published article, there was an error in the Funding statement. It was stated that no financial support was received for the research, authorship, and/or publication of this article. The correct Funding statement appears below. The author(s) declare that financial support was received for the research, authorship, and/or publication of this article. We acknowledge the financial support of the German Research Foundation (DFG) and the Open Access Publication Fund of Bielefeld University for the article processing charge. This work was supported by the DFG, as part of the SFB TRR 212 (NC3) – Project numbers 316099922 and 396780709; DFG project number 398434413; and DFG project number 433069365. The funding body played no role in the design of the study and collection, analysis, interpretation of data, and in writing the manuscript. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2024-06-28
Keywords: apicomplexa; avian malaria; black queen; chloroplasts; endosymbiosis; gametocyte sex ratio; genome copy abundance; mitochondria